Adhesive film, adhesive film with metal layer, wiring formation member, formation method for wiring layer, and wired member

JP2025024833APending Publication Date: 2025-02-21RESONAC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023129157
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-08
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0010】 本開示によれば、充分な耐クラック性を有し、対向する配線間を充分な導通性で接続することができとともに、高温条件下においても優れた接続性を有する接続部を形成することができる接着剤フィルム、充分な耐クラック性を有し、配線間を繋ぐ配線層の形成プロセスを簡略化することができるともに、高温条件下においても優れた接続性を有する配線層を形成することができる金属層付き接着剤フィルム及び配線形成用部材、並びに、これらを用いた配線層の形成方法、及び、配線形成部材を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025024833000001_ABST
    Figure 2025024833000001_ABST
Patent Text Reader

Abstract

To provide an adhesive film with a metal layer and a wiring formation member that feature sufficient crack resistance, enable the simplification of the formation process of a wiring layer interconnecting wires, and allows for the formation of the wiring layer with superior interconnectivity even at high temperatures.SOLUTION: A wiring formation member 1, one example of an adhesive film with a metal layer, comprises a metal layer 20 and an adhesive layer 10 that is provided on the metal layer 20. The adhesive layer 10 includes conductive particles 12 and a curable resin composition. A cured product of the adhesive layer 10 has a coefficient of thermal expansion of 1.5%-3% when heated from 40°C to 260°C.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an adhesive film, an adhesive film with a metal layer, a wiring-forming member, a method for forming a wiring layer, and a wiring-forming member. [Background technology]

[0002] Patent Document 1 discloses a method for manufacturing a printed wiring board incorporating electronic components such as IC chips. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-191204 A Summary of the Invention [Problem to be solved by the invention]

[0004] In a conventional method for manufacturing a component-embedded substrate, as shown in (a) and (b) of FIG. 8, insulating resin layers 102 and 103 are formed on both sides in the lamination direction of an electronic component 101 provided with an electrode 101a. Thereafter, as shown in (c) and (d) of FIG. 8, via electrodes 104 and 105 reaching the electrodes 101a of the electronic component 101 are formed in the insulating resin layers 102 and 103 by performing hole drilling with a laser, forming a plating layer, and forming an electrode by etching, etc. Then, as shown in (a) to (c) of FIG. 9, a component-embedded substrate 110 is formed by repeating the formation of further insulating resin layers 106 and 107, the formation of a via electrode 108 by hole drilling with a laser and forming a plating layer, and the formation of an electrode by etching, etc. In such a method for manufacturing a component-embedded substrate, however, many processes are performed to form one conductive layer (via electrode), and these processes must be repeated to form multiple conductive layers, making the manufacturing process very complicated.

[0005] Therefore, an adhesive having a metal layer such as a metal foil laminated thereon and conductive particles was examined as a member for forming wiring. With such a member for forming wiring, it is expected that a wiring layer connected to the wiring can be easily formed on the substrate on which the wiring is formed by going through a process of arranging the member for forming wiring on the substrate so that the adhesive layer faces the substrate on which the wiring is formed, a process of heat-pressing the member for forming wiring on the substrate, and a process of performing a patterning process on the metal layer.

[0006] Incidentally, in the above-mentioned component-embedded substrate used for semiconductor packages and the like, a load may be applied due to thermal expansion of the member in a high-temperature environment such as a reflow process. At this time, if an excessive load is applied to the connection portion formed as described above, an increase in connection resistance due to poor conduction, swelling, peeling, etc. becomes a problem. On the other hand, from the viewpoint of productivity and handling such as application to roll-to-roll, the wiring forming member is required to have crack resistance so that cracks do not occur during winding. In addition, crack resistance during winding is also necessary when slitting the member to a predetermined width. However, an adhesive layer designed with a resin that can form a connection portion with enhanced heat resistance tends to be difficult to obtain crack resistance.

[0007] Therefore, the present disclosure aims to provide an adhesive film that has sufficient crack resistance, can connect opposing wirings with sufficient conductivity, and can form a connection portion that has excellent connectivity even under high temperature conditions; an adhesive film with a metal layer and a wiring formation member that has sufficient crack resistance, can simplify the process of forming a wiring layer that connects wirings, and can form a wiring layer that has excellent connectivity even under high temperature conditions; and a method for forming a wiring layer using these, and a wiring formation member. [Means for solving the problem]

[0008] In order to solve the above problems, the present disclosure provides the following adhesive film, adhesive film with a metal layer, wiring-forming member, method for forming a wiring layer, and wiring-forming member.

[0009] [1] An adhesive film containing conductive particles and a thermosetting resin composition, wherein the adhesive film has a thermal expansion coefficient of 1.5 to 3% when a cured product of the adhesive film is heated from 40°C to 260°C. [2] The adhesive film according to [1], which has a reaction rate of 90% or less when heated at 180°C for 5 minutes. [3] The adhesive film according to [1] or [2], wherein the conductive particles include copper particles. [4] An adhesive film with a metal layer, comprising a metal layer and an adhesive layer disposed on the metal layer, the adhesive layer containing conductive particles and a thermosetting resin composition, and a thermal expansion coefficient of the cured adhesive layer when heated from 40°C to 260°C of 1.5 to 3%. [5] The adhesive film with a metal layer described in [4], wherein the adhesive layer has a reaction rate of 90% or less when heated at 180°C for 5 minutes. [6] The adhesive film with a metal layer according to [4] or [5], wherein the conductive particles include copper particles. [7] The metal layer-attached adhesive film according to any one of [4] to [6], which is used for forming wiring. [8] A wiring-forming member comprising an adhesive layer and a metal layer provided as separate bodies, the adhesive layer being capable of adhering to the metal layer during use, the adhesive layer comprising conductive particles and a thermosetting resin composition, and a thermal expansion coefficient of the cured adhesive layer when heated from 40°C to 260°C of 1.5 to 3%. [9] The member for forming wiring according to [8], wherein the adhesive layer has a reaction rate of 90% or less when heated at 180°C for 5 minutes.

[10] The member for forming a wiring according to [8] or [9], wherein the conductive particles include copper particles.

[11] A method for forming a wiring layer, comprising the steps of: preparing an adhesive film with a metal layer described in any one of [4] to [6]; preparing a substrate on which wiring is formed; placing the adhesive film with a metal layer on the surface of the substrate on which wiring is formed so as to cover the wiring, with the adhesive layer facing the substrate; heat-pressing the adhesive film with a metal layer to the substrate; and performing a patterning process on the metal layer.

[12] A method for forming a wiring layer, comprising the steps of: preparing a wiring-forming member according to any one of [8] to

[10] ; preparing a base material on which wiring is formed; placing the wiring-forming member on the surface of the base material on which wiring is formed so as to cover the wiring, with the adhesive layer facing the base material; heat-pressing the wiring-forming member to the base material; and performing a patterning process on the metal layer.

[13] A wiring-forming member comprising: a substrate having wiring; and a cured product of the adhesive layer of a metal layer-attached adhesive film described in any one of [4] to [6], which is placed on the substrate so as to cover the wiring, wherein the wiring is electrically connected to the metal layer of the metal layer-attached adhesive film or to another wiring formed from the metal layer.

[14] A wiring-forming member comprising: a substrate having wiring; and a cured product of the adhesive layer of the wiring-forming member according to any one of [8] to

[10] , which is disposed on the substrate so as to cover the wiring, wherein the wiring is electrically connected to the metal layer of the wiring-forming member or to another wiring formed from the metal layer. Effect of the Invention

[0010] According to the present disclosure, it is possible to provide an adhesive film that has sufficient crack resistance, can connect opposing wirings with sufficient conductivity, and can form a connection portion that has excellent connectivity even under high temperature conditions; an adhesive film with a metal layer and a wiring formation member that has sufficient crack resistance, can simplify the process of forming a wiring layer that connects wirings, and can form a wiring layer that has excellent connectivity even under high temperature conditions; and a method for forming a wiring layer using these, and a wiring formation member. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a cross-sectional view showing a wiring formation member according to an embodiment of the present disclosure. [Diagram 2] 2(a) to 2(d) are diagrams for sequentially explaining a method for forming a wiring layer using the wiring formation member shown in FIG. [Diagram 3] 3(a) to 3(c) are cross-sectional views showing wiring-forming members according to another embodiment of the present disclosure and the states when these wiring-forming members are pressure-bonded together. [Figure 4] FIG. 4 is a cross-sectional view showing a wiring formation member according to another embodiment of the present disclosure. [Diagram 5] 5(a) to 5(d) are diagrams for sequentially explaining a method for forming a wiring layer using the wiring formation member shown in FIG. [Figure 6] 6(a) and 6(b) are cross-sectional views illustrating an example in which a wiring layer is formed using the wiring formation member shown in FIG. [Figure 7] 7(a) and 7(b) are cross-sectional views illustrating another example in which a wiring layer is formed using the wiring formation member shown in FIG. [Figure 8] FIG. 8(a) to (d) are cross-sectional views for sequentially explaining a method for manufacturing a conventional component-embedded substrate. [Figure 9] 9(a) to 9(c) are cross-sectional views for sequentially explaining a method for manufacturing a conventional component-embedded substrate, showing steps subsequent to those in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the adhesive film with a metal layer and the member for forming a wiring according to one embodiment of the present disclosure, as well as the method for forming a wiring layer using them, and the adhesive film will be described with reference to the drawings. In the following description, the same or corresponding parts are given the same reference numerals, and duplicated descriptions will be omitted. Furthermore, unless otherwise specified, the positional relationship such as up, down, left, right, etc. will be based on the positional relationship shown in the drawings. Furthermore, the dimensional ratios of the drawings are not limited to the ratios shown in the drawings.

[0013] In the present specification, a numerical range indicated using "to" includes the numerical values ​​before and after "to" as the minimum and maximum values, respectively. In addition, in a numerical range described in stages in this specification, an upper limit or lower limit value described in one numerical range may be replaced with an upper limit or lower limit value of another numerical range described in stages. In addition, in a numerical range described in this specification, an upper limit or lower limit value of the numerical range may be replaced with a value shown in an example.

[0014] The adhesive film with a metal layer of this embodiment includes a metal layer and an adhesive layer disposed on the metal layer, the adhesive layer containing copper particles and a thermosetting resin composition, and the thermal expansion coefficient of the cured adhesive layer when heated from 40°C to 260°C is 1.5 to 3%. The adhesive film with a metal layer of this embodiment can be used to form wiring. In other words, the adhesive film with a metal layer of this embodiment may be a member for forming wiring. Hereinafter, the details of the adhesive film with a metal layer of this embodiment will be described with reference to the case where it is used as a member for forming wiring.

[0015] Fig. 1 is a cross-sectional view showing a wiring-forming member according to an embodiment of the present disclosure. As shown in Fig. 1, the wiring-forming member 1 is configured to include an adhesive layer 10 and a metal layer 20. The wiring-forming member 1 is a member that can be used when producing, for example, a rewiring layer, a build-up multilayer wiring board, and a component-embedded board, but is not limited thereto. The wiring-forming member 1 may also be used for EMI shielding, etc.

[0016] The adhesive layer 10 includes conductive particles 12 and an insulating adhesive component 14 in which the conductive particles 12 are dispersed. The adhesive component 14 of the adhesive layer 10 is defined as solid content other than conductive particles such as the conductive particles 12. The adhesive layer 10 may be in a B-stage state, i.e., a semi-cured state, before the wiring layer is formed by the wiring-forming member 1.

[0017] [Conductive particle composition] The conductive particles 12 are substantially spherical particles having electrical conductivity, and are composed of metal particles made of metals such as Au, Ag, Ni, Cu, solder, etc., or conductive carbon particles made of conductive carbon. The conductive particles 12 may be coated conductive particles having a core containing non-conductive glass, ceramic, plastic (polystyrene, etc.), etc., and a coating layer containing the above metal or conductive carbon and coating the core. Among these, the conductive particles 12 may be metal particles formed of a heat-fusible metal, or coated conductive particles having a core containing plastic, and a coating layer containing a metal or conductive carbon and coating the core. The conductive particles 12 may be copper particles from the viewpoint of making it difficult for a circuit to short circuit.

[0018] In one embodiment, the conductive particles 12 include a core made of a polymer particle (plastic particle) such as polystyrene, and a metal layer covering the core. The polymer particle may have substantially the entire surface covered with a metal layer, or a part of the surface of the polymer particle may be exposed without being covered with a metal layer, as long as the function as a connecting material is maintained. The polymer particle may be, for example, a particle containing a polymer containing at least one monomer selected from styrene and divinylbenzene as a monomer unit.

[0019] The metal layer may be formed of various metals such as Ni, Ni / Au, Ni / Pd, Cu, NiB, Ag, Ru, etc. The metal layer may be an alloy layer made of an alloy of Ni and Au, an alloy of Ni and Pd, etc. The metal layer may have a multilayer structure made of a plurality of metal layers. For example, the metal layer may be made of a Ni layer and an Au layer. The metal layer may be made by plating, vapor deposition, sputtering, soldering, etc. The metal layer may be a thin film (for example, a thin film formed by plating, vapor deposition, sputtering, etc.).

[0020] The conductive particle 12 may have an insulating layer. Specifically, for example, an insulating layer may be provided on the outer side of the coating layer in the conductive particle of the above embodiment, which includes a core (e.g., a polymer particle) and a coating layer such as a metal layer that coats the core. The insulating layer may be the outermost layer located on the outermost surface of the conductive particle. The insulating layer may be a layer formed from an insulating material such as silica or acrylic resin.

[0021] From the viewpoint of excellent dispersibility and conductivity, the average particle size Dp of the conductive particles 12 may be 1 μm or more, 2 μm or more, or 5 μm or more. From the viewpoint of excellent dispersibility and conductivity, the average particle size Dp of the conductive particles may be 50 μm or less, 30 μm or less, or 20 μm or less. From the above viewpoint, the average particle size Dp of the conductive particles may be 1 to 50 μm, 5 to 30 μm, 5 to 20 μm, or 2 to 20 μm.

[0022] The maximum particle size of the conductive particles 12 may be smaller than the minimum interval between electrodes in the wiring pattern (the shortest distance between adjacent electrodes). From the viewpoint of excellent dispersibility and conductivity, the maximum particle size of the conductive particles 12 may be 1 μm or more, 2 μm or more, or 5 μm or more. From the viewpoint of excellent dispersibility and conductivity, the maximum particle size of the conductive particles may be 50 μm or less, 30 μm or less, or 20 μm or less. From the above viewpoint, the maximum particle size of the conductive particles may be 1 to 50 μm, 2 to 30 μm, or 5 to 20 μm.

[0023] In this specification, the particle size of 300 random particles (pcs) is measured by observation using a scanning electron microscope (SEM), the average value of the particle sizes obtained is defined as the average particle size Dp, and the largest value obtained is defined as the maximum particle size of the particle. Note that when the particle has protrusions or the like and is not spherical in shape, the particle size is defined as the diameter of a circle circumscribing the particle in the SEM image.

[0024] The content of the conductive particles 12 is determined according to the fineness of the electrodes to be connected. For example, the amount of the conductive particles 12 is not particularly limited, but may be 0.1 volume % or more, 0.2 volume % or more, 1 volume % or more, 1.5 volume % or more, 2 volume % or more, 5 volume % or more, or 10 volume % or more based on the total volume of the adhesive components (components in the adhesive composition excluding the conductive particles). When the amount is within these ranges, resistance unevenness and low conductivity tend to be suppressed. The amount of the conductive particles 12 may be 30 volume % or less, 15 volume % or less, or 10 volume % or less based on the total volume of the adhesive components (components in the adhesive composition excluding the conductive particles 12). When the amount is within these ranges, short circuits tend to be less likely to occur. The "volume %" is determined based on the volume of each component before hardening at 23°C, but the volume of each component can be converted from weight to volume using specific gravity. Alternatively, the component can be poured into a measuring cylinder or the like containing a suitable solvent (water, alcohol, etc.) that will wet the component well without dissolving or swelling the component, and the increased volume can be calculated as the volume of the component.

[0025] From the viewpoint of reducing the connection resistance between the wirings, the adhesive layer 10 may contain copper particles as the conductive particles 12. In this case, the area of ​​the wiring layer to be formed becomes large (for example, 50 mm or more (2500 mm 2 If the pressure applied is more than 100 MPa, uneven springback of the copper particles is likely to occur due to uneven pressure, and connectivity under high temperature conditions is likely to decrease. However, by setting the thermal expansion coefficient of the cured product to a specific range, as described below, it is possible to form a wiring layer that has excellent connectivity under high temperature conditions while reducing the connection resistance.

[0026] The copper particles may be particles containing one or more of Cu and alloys of Cu and other metals. Examples of alloys of Cu and other metals include silver, zinc, nickel, gold, lead, tin, aluminum, manganese, beryllium, tungsten, and iron. From the viewpoint of reducing the connection resistance between wirings and reducing manufacturing costs, the content of Cu in the copper particles may be 50% by mass or more, 70% by mass or more, or 100% by mass.

[0027] The shape of the copper particles may be spherical, approximately spherical, flaky, columnar, rod-like, needle-like, plate-like, or fibrous.

[0028] The average particle size Dp of the copper particles may be 0.5 μm or more, 1 μm or more, or 3 μm or more from the viewpoint of reducing the connection resistance between wirings and from the viewpoint of increasing the definition of wirings. The average particle size Dp of the conductive particles may be 300 μm or less, 100 μm or less, or 50 μm or less from the viewpoint of improving insulation between adjacent wirings. From the above viewpoints, the average particle size Dp of the conductive particles may be 0.5 to 300 μm, 1 to 100 μm, or 3 to 50 μm.

[0029] The maximum particle size of the copper particles may be smaller than the minimum interval between electrodes in the wiring pattern (the shortest distance between adjacent electrodes). The maximum particle size of the copper particles may be 0.5 μm or more, 1 μm or more, or 3 μm or more from the viewpoint of reducing the connection resistance value between wirings. The maximum particle size of the conductive particles may be 300 μm or less, 100 μm or less, or 50 μm or less from the viewpoint of improving insulation between adjacent wirings. From the above viewpoint, the maximum particle size of the conductive particles may be 0.5 to 300 μm, 1 to 100 μm, or 3 to 50 μm.

[0030] The content of the copper particles can be 6% by volume or less based on the total volume of the adhesive layer from the viewpoint of reducing the connection resistance. When the content of the copper particles is 6% by volume or less, the copper particles can be sufficiently flattened, and thus the connection area with the electrode or wiring provided on the substrate and the metal layer can be sufficiently secured. It is generally considered that the connection resistance decreases as the content of the conductive particles increases, but in the case of copper particles, when the content exceeds 6% by volume, it becomes difficult to flatten the particles, making it difficult to reduce the connection resistance. This is a finding clarified by the present inventors' study, and can be said to be unexpected. The content of the copper particles may be 0.1 to 6% by volume, or 0.5 to 3% by volume, from the viewpoints of reducing the connection resistance, improving the insulation between adjacent wiring, and reducing the manufacturing cost.

[0031] From the viewpoint of reducing the connection resistance, the conductive particles 12 may satisfy one or more of the following conditions. From the viewpoint of easily obtaining good connectivity between wirings, the adhesive layer 10 may contain copper particles that satisfy one or more of the following conditions. (i) The change in size when a pressure of 50 mN is applied per particle is 1 to 5 μm. (ii) After a pressure of 50 mN is applied per particle, the recovery amount when the pressure is released is 1 μm or less. (iii) The recovery rate, calculated by (amount of recovery when a pressure of 50 mN is applied per particle and then released) × 100 / (amount of change when a pressure of 50 mN is applied per particle), is 1 to 25%.

[0032] The above-mentioned change and recovery amounts are determined by a microcompression test using a probe, and refer to values ​​measured under the following conditions. Measurement device: "FISCHERSCOPE HM2000" (manufactured by Fisher Instruments) Probe size (area): 100 μm x 100 μm Pressing time: Press for 50 seconds / Return for 50 seconds Measurement temperature: 25℃ Thrust: 50mN

[0033] [Adhesive layer / adhesive component composition] The adhesive component 14 constituting the adhesive layer 10 may be a thermosetting resin composition. Components contained in the thermosetting resin composition include a thermosetting resin, a curing agent, and a curing accelerator.

[0034] The thermosetting resin is a resin that exhibits hardening by heat. Examples of the thermosetting resin include epoxy resin, polyimide resin, triazine resin such as melamine resin, phenol resin, and modified products of these resins. Among these, epoxy resin may be used from the viewpoint of sufficiently suppressing the occurrence of bubbles or peeling during wiring formation.

[0035] The adhesive component may contain an epoxy resin and a phenol resin as thermosetting components, from the viewpoint of sufficiently suppressing the occurrence of bubbles or peeling during wiring formation and making it difficult for resistance unevenness to occur.

[0036] The epoxy resin may be any compound having two or more epoxy groups in the molecule, and examples thereof include bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, biphenyl type epoxy resin, biphenyl novolac type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, bisphenol A novolac type epoxy resin, bisphenol F novolac type epoxy resin, naphthalene type multifunctional epoxy resin, dicyclopentadiene type epoxy resin, alicyclic epoxy resin, aliphatic chain epoxy resin, glycidyl ester type epoxy resin, isocyanurate type epoxy resin, hydantoin type epoxy resin, glycidyl ether compound of multifunctional phenol, glycidyl ether compound of bifunctional alcohol, and hydrogenated products thereof. Among these, novolac type epoxy resins such as biphenyl novolac type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, bisphenol A novolac type epoxy resin, or bisphenol F novolac type epoxy resin may be used from the viewpoint of ease of handling and availability. The epoxy resin may be used alone or in combination of two or more kinds.

[0037] From the viewpoint of ensuring adhesive strength and heat resistance, the adhesive component may contain, as an epoxy resin, a compound having three or more epoxy groups in one molecule.

[0038] From the viewpoints of ensuring adhesive strength and heat resistance, and good reactivity, the epoxy resin may have an epoxy equivalent of 100 to 1000 g / eq, 125 to 900 g / eq, or 150 to 800 g / eq. The epoxy equivalent is determined by a method standardized in the JIS standard (K7236:2001).

[0039] The content of the epoxy resin in the adhesive component may be 5 to 95 mass %, 10 to 90 mass %, 15 to 85 mass %, or 40 to 60 mass %, based on the total amount of the adhesive component (total amount of solids other than the conductive particles in the adhesive layer 10).

[0040] The phenolic resin functions as a curing agent for the epoxy resin. Examples of the phenolic resin include novolac-type phenolic resins such as phenol novolac, cresol novolac, bisphenol A novolac, bisphenol F novolac, and catechol novolac, and those in which the aromatic ring is substituted with an alkyl group. The phenolic resin may be used alone or in combination of two or more kinds.

[0041] From the viewpoint of ensuring adhesive strength and heat resistance, the adhesive component may contain a compound having three or more phenol groups or cresol groups in one molecule as a phenol resin. As such a compound, from the viewpoint of ease of handling and availability, phenol novolac type phenol resin, cresol novolac type phenol resin, bisphenol A novolac type phenol resin, bisphenol F novolac type phenol resin, or the like may be used.

[0042] The hydroxyl group equivalent of the phenolic resin may be 300 g / eq or less or 250 g / eq or less from the viewpoint of suppressing the occurrence of bubbles or peeling during wiring formation and making it difficult for resistance unevenness to occur, and may be 50 g / eq or more or 100 g / eq or more from the viewpoint of ease of handling and good reactivity.

[0043] The hydroxyl equivalent of the phenol resin is determined by the following measurement method. <Method for measuring hydroxyl equivalent> Accurately weigh out 1 g of sample into a round-bottom flask, then accurately weigh out 5 mL of acetic anhydride and pyridine test solution. Next, attach an air condenser to the flask and heat it at 100°C for 1 hour. After cooling the flask, add 1 mL of water and heat the flask again at 100°C for 10 minutes. After cooling the flask again, rinse the air condenser and the neck of the flask with 5 mL of neutralized methanol, and add 1 mL of phenolphthalein reagent. The solution thus obtained is titrated with 0.1 mol / L potassium hydroxide-ethanol solution to determine the hydroxyl value. From the obtained hydroxyl value, calculate the hydroxyl equivalent (g / eq) converted to the mass per 1 mole (1 eq) of hydroxyl groups.

[0044] The content of the phenol resin in the adhesive component can be set so that the number of hydroxyl groups in the phenol resin is 0.5 to 2 per epoxy group in the epoxy resin.

[0045] The adhesive component containing the epoxy resin and the phenol resin may further contain a thermosetting resin other than the epoxy resin, and may further contain a curing agent other than the phenol resin. As the thermosetting resin other than the epoxy resin, polyimide resin, triazine resin such as melamine resin, and modified products of these resins can be used. As the curing agent other than the phenol resin, amines, amides, acid anhydrides, acids, imidazoles, etc. can be mentioned.

[0046] In the wiring-forming member of this embodiment, the adhesive component may further contain a maleimide compound from the viewpoint of sufficiently suppressing the occurrence of bubbles or peeling during wiring formation.

[0047] In this case, from the viewpoint of sufficiently suppressing the occurrence of bubbles or peeling during wiring formation, the adhesive component may contain an epoxy resin as a thermosetting resin. In this case, the content of the epoxy resin in the adhesive component may be 5 to 95 mass %, 10 to 90 mass %, 15 to 85 mass %, or 15 to 40 mass % based on the total amount of the adhesive component (total amount of solids other than the conductive particles in the adhesive layer 10).

[0048] The maleimide compound is a compound having at least one N-substituted maleimide group in one molecular structure. The maleimide compound may contain at least one selected from the group consisting of a polymaleimide compound (m1) (hereinafter, sometimes referred to as "(m1) component") having at least two N-substituted maleimide groups in one molecular structure and its derivatives. Examples of the "derivatives" include an addition reaction product between the polymaleimide compound (m1) and an amine compound such as a diamine compound described later. Since maleimide compounds have low reactivity, it is expected that the curing reaction will proceed slowly by containing them in the adhesive component 14. The slow progress of the curing reaction can ensure sufficient flow time, making it possible to sufficiently suppress the occurrence of bubbles or peeling during wiring formation.

[0049] Examples of the component (m1) include N,N'-ethylene bismaleimide, N,N'-hexamethylene bismaleimide, N,N'-(1,3-phenylene) bismaleimide, N,N'-[1,3-(2-methylphenylene)] bismaleimide, N,N'-[1,3-(4-methylphenylene)] bismaleimide, N,N'-(1,4-phenylene) bismaleimide, bis(4-maleimidophenyl)methane, bis(3-methyl-4-maleimidophenyl)methane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethane bismaleimide, bis(4- maleimidophenyl) ether, bis(4-maleimidophenyl) sulfone, bis(4-maleimidophenyl) sulfide, bis(4-maleimidophenyl) ketone, bis(4-maleimidocyclohexyl) methane, 1,4-bis(4-maleimidophenyl) cyclohexane, 1,4-bis(maleimidomethyl) cyclohexane, 1,4-bis(maleimidomethyl) benzene, 1,3-bis(4-maleimidophenoxy) benzene, 1,3-bis(3-maleimidophenoxy) benzene, bis[4-(3-maleimidophenoxy)phenyl] methane, bis[ 4-(4-maleimidophenoxy)phenyl]methane, 1,1-bis[4-(3-maleimidophenoxy)phenyl]ethane, 1,1-bis[4-(4-maleimidophenoxy)phenyl]ethane, 1,2-bis[4-(3-maleimidophenoxy)phenyl]ethane, 1,2-bis[4-(4-maleimidophenoxy)phenyl]ethane, 2,2-bis[4-(3-maleimidophenoxy)phenyl]propane, 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane, 2,2-bis[4-(3-maleimidophenoxy)phenyl]buta , 2,2-bis[4-(4-maleimidophenoxy)phenyl]butane, 2,2-bis[4-(3-maleimidophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(4-maleimidophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 4,4-bis(3-maleimidophenoxy)biphenyl, 4,4-bis(4-maleimidophenoxy)biphenyl, bis[4-(3-maleimidophenoxy)phenyl]ketone, bis[4-(4-maleimidophenoxy)phenyl]ketone, 2,2-bis(4-maleimidophenyl) disulfide, bis(4-maleimidophenyl) disulfide, bis[4-(3-maleimidophenoxy)phenyl] sulfide, bis[4-(4-maleimidophenoxy)phenyl] sulfide, bis[4-(3-maleimidophenoxy)phenyl] sulfoxide, bis[4-(4-maleimidophenoxy)phenyl] sulfoxide, bis[4-(3-maleimidophenoxy)phenyl] sulfone, bis[4-(4-maleimidophenoxy)phenyl] sulfone, bis[4-(3-maleimidophenoxy)phenyl] ether, bis[4-(4-maleimidophenoxy)phenyl] ether, 1,4-bis[4-(4-maleimidophenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-maleimidophenoxy)-α,α -dimethylbenzyl]benzene, 1,4-bis[4-(3-maleimidophenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(3-maleimidophenoxy)-α,α-dimethylbenzyl]benzene, 1,4-bis[4-(4-maleimidophenoxy)-3,5-dimethyl-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-maleimidophenoxy)-3,5-dimethyl-α,α-dimethylbenzyl]benzene, 1,4-bis[4-(3-maleimidophenoxy)-3,5-dimethyl-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(3-maleimidophenoxy)-3,5-dimethyl-α,α-dimethylbenzyl]benzene, and polyphenylmethane maleimide (for example, manufactured by Daiwa Kasei Co., Ltd., trade name: BMI-2300, etc.). The maleimide compound may be used alone or in combination of two or more kinds.

[0050] Among these maleimide compounds, bis(4-maleimidophenyl)methane, bis(4-maleimidophenyl)sulfone, N,N'-(1,3-phenylene)bismaleimide, 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane, or polyphenylmethanemaleimide are preferred, as they have a high reactivity and can be made more heat resistant. In terms of solubility in solvents, bis(4-maleimidophenyl)methane is particularly preferred.

[0051] From the viewpoints of solubility in organic solvents, compatibility, and adhesion to metal foils, the maleimide compound may contain a derivative of a polymaleimide compound (m1). The derivative of the polymaleimide compound (m1) may contain, for example, a modified polymaleimide compound (M) having a structural unit derived from the polymaleimide compound (m1) and a structural unit derived from an amine compound (m2) having an amino group (hereinafter sometimes referred to as "component (m2)"). The modified polymaleimide compound (M) can also be said to be an addition reaction product of the component (m1) and the component (m2). The structural unit derived from the component (m1) and the structural unit derived from the component (m2) contained in the modified polymaleimide compound (M) may each be one type or a combination of two or more types.

[0052] The modified polymaleimide compound (M) may be a compound having a structure represented by the following formula (1), which is formed by an addition reaction between a maleimide group in the component (m1) and an amino group in the component (m2), where * indicates a bond position.

[0053] [ka]

[0054] The component (m2) is preferably an amine compound (polyamine compound) having at least two amino groups, and may be a diamine compound having two amino groups. Examples of the component (m2) include 4,4'-diaminodiphenylmethane, 4,4'-diamino-3,3'-dimethyldiphenylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl ketone, 4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4' -Diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, 2,2-bis(3-amino-4-hydroxyphenyl)propane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 2,2-bis(4-aminophenyl)propane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 1,3-bis(3-aminophenoxy)benzidine, Zene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, 1,3-bis[1-[4-(4-aminophenoxy)phenyl]-1-methylethyl]benzene, 1,4-bis[1-[4-(4-aminophenoxy)phenyl]-1-methylethyl]benzene, 4,4'-[1,3-phenylenebis(1-methylethylidene)]bis Examples of the aromatic diamine compounds include aniline, 4,4'-[1,4-phenylenebis(1-methylethylidene)]bisaniline, 3,3'-[1,3-phenylenebis(1-methylethylidene)]bisaniline, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, and 9,9-bis(4-aminophenyl)fluorene; and amine compounds having a siloxane skeleton.

[0055] Among these, the component (m2) may be an amine compound having a siloxane skeleton from the viewpoint of low thermal expansion. That is, the modified polymaleimide compound (M) may have a structural unit derived from the polymaleimide compound (m1) and a structural unit derived from an amine compound having a siloxane skeleton.

[0056] The component (m2) may be a compound represented by the following general formula (2).

[0057] [ka]

[0058] In formula (2), X b4 represents a divalent organic group.

[0059] From the viewpoint of low thermal expansion, the component (m2) is X in the above general formula (2). b4 may contain an amine compound having a siloxane skeleton having a structural unit represented by the following general formula (3). b4 may contain an amine compound having a siloxane skeleton having a structural unit (or group) represented by the following general formula (4).

[0060] [ka]

[0061] In formula (3), R b16 and R b17 each independently represents an alkyl group having 1 to 5 carbon atoms, a phenyl group, or a substituted phenyl group. * indicates the bonding position.

[0062] [ka]

[0063] In formula (4), R b16 and R b17 is R in the above general formula (3). b16 and Rb17 Synonymous with R, which exists in multiple places. b16 and R b17 may be the same or different. b18 and R b19 each independently represents an alkyl group having 1 to 5 carbon atoms, a phenyl group, or a substituted phenyl group. b9 and X b10 each independently represents a divalent organic group; b13 represents an integer from 2 to 100.

[0064] R b16 , R b17 , R b18 , and R b19 Examples of the substituent in the substituted phenyl group represented by the formula: include an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, and an alkynyl group having 2 to 5 carbon atoms.

[0065] X b9 and X b10 Examples of the divalent organic group represented by the formula (I) include an alkylene group, an alkenylene group, an alkynylene group, an arylene group, -O-, or a divalent linking group formed by combining these groups.

[0066] The content of the structural unit derived from the (m1) component in the modified polymaleimide compound (M) is not particularly limited, but may be 50 to 95 mass %, 70 to 92 mass %, or 75 to 90 mass %.

[0067] The content of the structural unit derived from the (m2) component in the modified polymaleimide compound (M) is not particularly limited, but may be 5 to 50 mass %, 8 to 30 mass %, or 10 to 25 mass %.

[0068] The total content of the structural units derived from the (m1) component and the structural units derived from the (m2) component in the modified polymaleimide compound (M) is not particularly limited, and may be 80 mass % or more, 90 mass % or more, 95 mass % or more, or 100 mass % (i.e., consisting only of structural units derived from the (m1) component and structural units derived from the (m2) component).

[0069] The content of the maleimide compound in the adhesive component may be 5 to 95 mass %, 10 to 90 mass %, or 15 to 85 mass %, based on the total amount of the adhesive component (total amount of solids other than the conductive particles in the adhesive layer 10).

[0070] Examples of the curing accelerator include imidazole compounds, organic phosphorus compounds, tertiary amines, and quaternary ammonium salts. The curing accelerator may be used alone or in combination of two or more. The adhesive component may contain an imidazole compound as a curing accelerator from the viewpoint of being able to arbitrarily adjust the temperature and time during use (for example, the heating temperature and heating time during thermocompression bonding).

[0071] The content of the curing accelerator in the adhesive component may be 0.001 to 10% by mass based on the total amount of the adhesive component.

[0072] The adhesive component 14 may contain other components in addition to the above-mentioned thermosetting component, such as a filler, an antioxidant, a film-forming material, a softener, an anti-aging agent, a colorant, a flame retardant, a thixotropic agent, and a coupling agent.

[0073] Examples of the filler include inorganic fillers and organic fillers. Examples of the inorganic filler include alumina, silica, titanium oxide, clay, calcium carbonate, aluminum carbonate, magnesium silicate, aluminum silicate, mica, glass short fiber, aluminum borate, silicon carbide, etc. Examples of the organic filler include silicone particles, methacrylate-butadiene-styrene particles, acrylic-silicone particles, polyamide particles, polyimide particles, etc. The filler may be used alone or in combination of two or more.

[0074] The adhesive component may contain silica particles as a filler from the standpoint of improving heat resistance, improving mechanical properties, and adjusting flowability during use (for example, during heat and pressure bonding).

[0075] The maximum diameter of the filler may be less than the particle diameter of the conductive particles 12, and may be 0.001 to 10 μm.

[0076] The content of the filler may be 5 to 60 parts by volume relative to 100 parts by volume of the adhesive component. When the content of the filler is 5 to 60 parts by volume, good connection reliability tends to be obtained.

[0077] Examples of the antioxidant include quinone derivatives such as benzoquinone and hydroquinone, phenol derivatives (hindered phenol derivatives) such as 4-methoxyphenol and 4-t-butylcatechol, aminoxyl derivatives such as 2,2,6,6-tetramethylpiperidine-1-oxyl and 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl, and hindered amine derivatives such as tetramethylpiperidyl methacrylate.

[0078] The content of the antioxidant may be 0.01% by mass to 5% by mass, or 0.1% by mass to 3% by mass, based on the total amount of the adhesive components.

[0079] As the film-forming material, a thermoplastic resin is preferably used, and examples thereof include phenoxy resin, polyvinyl formal resin, polystyrene resin, polyvinyl butyral resin, polyester resin, polyamide resin, xylene resin, polyurethane resin, polyacrylic resin, polyester urethane resin, etc. Furthermore, these polymers may contain siloxane bonds or fluorine substituents. These resins may be used alone or in combination of two or more kinds. Among the above resins, phenoxy resin may be used from the viewpoints of adhesive strength, compatibility, heat resistance, and mechanical strength.

[0080] The larger the molecular weight of the thermoplastic resin, the easier it is to obtain film formability, and the melt viscosity that affects the fluidity of the film can be set in a wide range. The molecular weight of the thermoplastic resin may be 5,000 to 150,000, or 10,000 to 80,000, in terms of weight average molecular weight. By setting the weight average molecular weight to 5,000 or more, good film formability is easily obtained, and by setting it to 150,000 or less, good compatibility with other components is easily obtained.

[0081] In the present disclosure, the weight average molecular weight refers to a value measured by gel permeation chromatography (GPC) using a calibration curve based on standard polystyrene under the following conditions. (Measurement conditions) Equipment: Tosoh Corporation GPC-8020 Detector: Tosoh RI-8020 Column: Gelpack GLA160S+GLA150S manufactured by Hitachi Chemical Co., Ltd. Sample concentration: 120mg / 3mL Solvent: Tetrahydrofuran Injection volume: 60μL Pressure: 2.94 x 106 Pa (30 kgf / cm 2 ) Flow rate: 1.00mL / min

[0082] The content of the film-forming material may be 0.5 to 75% by mass, or 1 to 50% by mass, based on the total amount of the adhesive components.

[0083] From the viewpoint of improving storage stability and connection reliability, the adhesive component 14 may be substantially free of highly reactive radical polymerizable compounds such as acrylic compounds, methacrylic compounds, styrene compounds, and vinyl compounds. Note that "substantially free" means that the content is 1% by mass or less based on the total amount of the adhesive component. The content of the above compounds in the adhesive component may be 0.5% by mass or less, or may be 0% by mass, based on the total amount of the adhesive component.

[0084] From the viewpoint of forming a wiring layer having sufficient crack resistance and excellent connectivity under high temperature conditions, the adhesive layer 10 has a thermal expansion coefficient of 1.5 to 3% when the cured product is heated from 40° C. to 260° C. The thermal expansion coefficient can be determined by the following procedure. [Preparation of cured product] (1) Before heating, a portion of the adhesive layer was scraped off and 0.60 g was weighed out as an evaluation sample. (2) Prepare a silicone sheet that is 100 mm long, 100 mm wide, and 1 mm thick, and cut out a portion of this sheet to measure 5 mm x 40 mm x 1 mm. (3) Place the pre-heating evaluation sample measured in (1) into the cut-out portion of the silicone sheet. (4) The silicone sheet containing the pre-heating evaluation sample is heated and pressurized for 60 minutes at 180° C. and 2 MPa using a thermocompression bonding device to produce a cured product of the pre-heating evaluation sample. [Measurement of thermal expansion coefficient of cured product] (1) The cured product of the pre-heated evaluation sample prepared above is cut into a piece measuring 5 mm x 5 mm x 1 mm to prepare an evaluation sample. (2) Using a thermomechanical analysis (TMA) device (measurement mode: compression), measure the change in thickness when the evaluation sample is heated from 40°C to 260°C at a heating rate of 5°C / min, and calculate the thermal expansion coefficient using the following formula. Thermal expansion coefficient (%) = (thickness at 260°C - thickness at 40°C) x 100 / (thickness at 40°C)

[0085] If the thermal expansion coefficient is 1.5% or more, it is easy to improve the crack resistance of the adhesive layer, and if the thermal expansion coefficient is 3% or less, the wiring layer can have excellent connectivity under high humidity conditions. From the viewpoint of achieving a high level of both the crack resistance of the adhesive layer and good connectivity of the wiring layer under high temperature conditions, the thermal expansion coefficient may be 1.6 to 2.9%, or 1.7 to 2.8%.

[0086] The above-mentioned thermal expansion coefficient can be adjusted, for example, by the following method. (a) Methods for increasing the coefficient of thermal expansion include increasing the amount of thermoplastic resin components, reducing the amount of fillers, adding low-elasticity components such as rubber components or elastomer components, and reducing the amount of crosslinkable components when cured. (b) Methods for reducing the coefficient of thermal expansion include reducing the amount of thermoplastic resin components, increasing the amount of fillers, reducing the amount of low elasticity components, and increasing the amount of components that crosslink when cured.

[0087] In order to prevent uneven resistance, the adhesive layer 10 may have a reaction rate of 90% or less, 85% or less, 80% or less, or 70% or less when heated at 180°C for 5 minutes.

[0088] The above reaction rate refers to a value determined by the following measurement method. [Measurement of reaction rate when heated at 180℃ for 5 minutes] A part of the adhesive layer is scraped off to obtain two 5 mg samples for evaluation before heating. Next, one of the samples for evaluation before heating is heated at 180°C for 5 minutes to obtain a sample for evaluation after heating. For each of the samples for evaluation before heating and the samples for evaluation after heating, a differential scanning calorimetry (DSC) device (product name DSC7, manufactured by PERKIN ELMER) is used to measure the DSC calorific value under a nitrogen gas flow at a measurement temperature range of 30°C to 250°C and a heating rate of 2°C / min. Based on the measured DSC calorific value, the reaction rate when heated at 180°C for 5 minutes is calculated using the following formula. Reaction rate = (Cx-Cy) x 100 / Cx [In the formula, Cx represents the DSC calorific value (J / g) of the evaluation sample before heating, and Cy represents the DSC calorific value (J / g) of the evaluation sample after heating.]

[0089] The reaction rate of the adhesive layer when heated at 180°C for 5 minutes can be reduced by, for example, adding the above-mentioned phenolic resin or maleimide compound, not adding a curing accelerator, or selecting a curing accelerator with a high reaction initiation temperature.

[0090] From the viewpoint of preventing uneven resistance, the ratio [Dp / T] of the average particle size Dp of the copper particles to the thickness T of the adhesive layer may be 0.56 to 1.2, 0.6 to 1.15, or 0.65 to 1.1.

[0091] The thickness of the adhesive layer may be 1 to 70 μm, may be 2 to 60 μm, or may be 3 to 50 μm.

[0092] [Metal layer composition] The surface roughness Rz of one surface of the metal layer 20 and the opposite surface may be equal or different. The metal layer 20 has a thickness of, for example, 5 μm to 200 μm. The thickness of the metal layer here includes the surface roughness Rz. The metal layer 20 is, for example, copper foil, aluminum foil, nickel foil, stainless steel, titanium, or platinum.

[0093] The adhesive layer 10 is disposed on the first surface 20a of the metal layer 20. The surface roughness Rz of the first surface 20a of the metal layer 20 may be 0.3 μm or more, 0.5 μm or more, or 1.0 μm or more. The surface roughness Rz of the first surface 20a of the metal layer 20 may be 50 μm or less, 40 μm or less, 30 μm or less, 20 μm or less, less than 20 μm, 17 μm or less, 10 μm or less, 8.0 μm or less, 5.0 μm or less, or 3.0 μm or less. The surface roughness Rz of the first surface 20a of the metal layer 20 may be, for example, 0.3 μm or more and 20 μm or less, 0.3 μm or more and less than 20 μm, and more specifically, 0.5 μm or more and 10 μm or less. The surface roughness Rz of the second surface 20b of the metal layer 20 may be, for example, 20 μm or more, may be rougher than the surface roughness Rz of the first surface 20a, may be the same surface roughness as the first surface 20a, or may not be rougher than the surface roughness Rz of the first surface 20a. If the surface roughness Rz of the first surface 20a of the metal layer 20 is too smooth (for example, the surface roughness Rz is 0.2 μm), the adhesion between the metal layer 20 and the adhesive layer 10 may not be maintained for a long period of time and may peel off. For this reason, the surface roughness Rz of the first surface 20a of the metal layer 20 may be 0.3 μm or more. However, the surface roughness Rz of the first surface 20a of the metal layer 20 may be less than 0.3 μm by adopting a material or connection configuration that can ensure adhesion.

[0094] Surface roughness Rz refers to the ten-point average roughness Rzjis measured according to the method specified in the JIS standard (JIS B 0601-2001), and refers to the value measured using a commercially available surface roughness profile measuring instrument. For example, it can be measured using a nano search microscope (Shimadzu Corporation's "SFT-3500").

[0095] Here, the relationship between the average particle diameter Dp of the conductive particles 12 and the surface roughness Rz of the first surface 20a of the metal layer 20 will be described below. In this embodiment, the "surface roughness / average particle diameter" which is the ratio of the surface roughness Rz of the first surface 20a of the metal layer 20 to the average particle diameter Dp of the conductive particles 12 may be 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.1 or more, 0.2 or more, 0.3 or more, 0.5 or more, or 1 or more. In addition, the "surface roughness / average particle diameter" which is the ratio of the surface roughness Rz of the first surface 20a of the metal layer 20 to the average particle diameter Dp of the conductive particles 12 may be 3 or less, 2 or less, 1.7 or less, or 1.5 or less. The "surface roughness / average particle size", which is the ratio of the surface roughness Rz of the first surface 20a of the metal layer 20 to the average particle size Dp of the conductive particles 12, may be, for example, 0.05 or more and 3 or less, and more specifically, 0.06 or more and 2 or less. In this embodiment, the surface roughness Rz of the first surface 20a of the metal layer 20 and the average particle size Dp of the conductive particles 12 may be controlled so that the "surface roughness / average particle size", which is the ratio of the surface roughness Rz of the first surface 20a of the metal layer 20 to the average particle size Dp of the conductive particles 12, is in the range of 0.05 to 3.

[0096] Another aspect of the present disclosure relates to a method for forming a wiring layer using a member for forming a wiring. The method for forming a wiring layer using the above-mentioned member for forming a wiring 1 will be described with reference to Fig. 2. (a) to (d) of Fig. 2 are diagrams showing a method for forming a wiring layer using the member for forming a wiring shown in Fig. 1.

[0097] First, as shown in (a) of Fig. 2, a wiring-forming member 1 is prepared. Furthermore, a base material 30 on which wiring 32 is formed is prepared. Then, the wiring-forming member 1 is arranged so that the adhesive layer 10 side of the wiring-forming member 1 faces the base material 30. Thereafter, as shown in (b) of Fig. 2, lamination is performed so as to cover the wiring 32, and the wiring-forming member 1 is attached onto the base material 30.

[0098] Next, as shown in FIG. 2(c), the wiring forming member 1 is heated and pressed to a predetermined extent, and is pressed against the substrate 30. At this time, if the first surface 20a of the metal layer 20 of the wiring forming member 1 is flat, the conductive particles 12 that need to ensure electrical conductivity can be more reliably deformed into flat conductive particles 12a. Then, in the pressed wiring forming member 1a, the flattened conductive particles 12a (whereby the insulating layer is destroyed and the conductive portion is exposed) are arranged on the wiring 32, and reliable electrical conduction between the metal layer 20 and the wiring 32 is achieved. At this time, the adhesive layer 10 is also crushed to become a thinner adhesive layer 10A.

[0099] 2(d), the metal layer 20 is subjected to a predetermined patterning process (e.g., etching process) to process it into a predetermined wiring pattern 20c (another wiring). At this time, the second surface 20b of the metal layer 20 may be processed to have a smooth surface. The above-mentioned processes of FIG. 2(a) to (d) may be repeated a predetermined number of times to form a wiring layer.

[0100] That is, a method for forming a wiring layer using a wiring forming member includes the steps of preparing a wiring forming member, preparing a base material on which wiring is formed, placing the wiring forming member on the surface of the base material on which wiring is formed so that the adhesive layer side faces the substrate and covers the wiring, heating and pressing the wiring forming member to the base material, and performing a patterning process on the metal layer.

[0101] In this manner, the wiring-forming member 1b is formed. The wiring-forming member 1b includes a base material 30 having wiring 32, and a cured product of the adhesive component 14 of the wiring-forming member 1 (adhesive layer of the wiring-forming member bonded by heating and pressure) disposed on the base material 30 so as to cover the wiring 32. In the wiring-forming member 1b, the wiring 32 and the metal layer 20 of the wiring-forming member 1 or the wiring 20c formed (for example, by etching) from the metal layer 20 are electrically connected by the conductive particles 12a. When the processes (a) to (d) in FIG. 2 are repeated a predetermined number of times, the wiring-forming member 1b may have a configuration having a plurality of wiring layers (layers in which the above-mentioned wirings are connected to each other).

[0102] Thus, according to the method for forming a wiring layer using the wiring formation member 1 according to this embodiment, the process for forming a wiring layer connecting between wirings can be simplified compared to the conventional process of performing laser processing and filling plating, etc. Also, the formed wiring layer can be easily thinned.

[0103] Furthermore, according to the method for forming a wiring layer using the wiring formation member 1 of this embodiment, when the adhesive layer 10 has the above-mentioned reaction rate and the ratio [Dp / T] of the average particle size Dp of the conductive particles 12 to the thickness T of the adhesive layer 10 is 0.56 to 1.2, a wiring layer in which resistance unevenness is suppressed can be formed.

[0104] Although the embodiments of the present disclosure have been described in detail above, the present disclosure is not limited to the above embodiments and can be applied to various embodiments. For example, in the above embodiment, as shown in (a) of FIG. 3, the conductive particles 12 are randomly or evenly dispersed in the adhesive layer 10 in the wiring forming member 1, but as shown in (b) of FIG. 3, the conductive particles 12 may be arranged (distributed) on the metal layer 20 side. In this case, in the adhesive layer 10, the conductive particles 12 are not exposed on the second surface 10b opposite to the metal layer 20, and the thickness of the adhesive layer 10 existing between the conductive particles 12 and the first surface 20a of the metal layer 20 may be greater than 0 μm or 0.1 μm and less than 1 μm. In this case, since the conductive particles 12 are arranged on the metal layer 20 side, it is possible to more reliably crush the conductive particles 12 into a flat shape by the metal layer 20 in the wiring layer 1d. In addition, by distributing the conductive particles 12 on the metal layer 20 side in this way, the capture rate of the conductive particles 12 to the wiring (electrode) or the like can be improved. That is, the conduction can be made more stable. The distance between the conductive particle 12 and the first surface 20a of the metal layer 20 (the thickness of the adhesive layer 10 between them) means the shortest distance from the surface of the metal layer 20 in contact with the adhesive layer 10 to the surface of the conductive particle 12, and is, for example, an average value at any 30 points. This distance is measured by sandwiching the wiring forming member between two pieces of glass (thickness: about 1 mm), casting a resin composition consisting of 100 g of bisphenol A type epoxy resin (product name: JER811, manufactured by Mitsubishi Chemical Corporation) and 10 g of a hardener (product name: Epomount hardener, manufactured by Refine Tech Co., Ltd.), polishing the cross section with a polishing machine, and using a scanning electron microscope (SEM, product name: SE-8020, manufactured by Hitachi High-Tech Science Corporation).

[0105] Also, as shown in FIG. 3(c), the adhesive layer 10d may be divided into a first adhesive layer 10e and a second adhesive layer 10f. The adhesive components constituting the first adhesive layer 10e and the second adhesive layer 10f may be the same as the adhesive components constituting the adhesive layer 10 described above, but the difference is that the conductive particles 12 are not dispersed, i.e., are not included, in the second adhesive layer 10f. In this case, if the adhesive layer 10d has the above-mentioned reaction rate and the ratio [Dp / T] of the average particle diameter Dp of the conductive particles 12 to the thickness T of the adhesive layer 10 is 0.56 to 1.2, a wiring layer with suppressed resistance unevenness can be formed. In the wiring forming member 1e according to this modification, the conductive particles 12 are dispersed, i.e., included, in the first adhesive layer 10e. In this case, as in the modification shown in FIG. 3(b), the conductive particles 12 are arranged on the metal layer 20 side, so that the conductive particles 12 can be more reliably crushed into a flat shape by the metal layer 20 in the wiring layer 1f. In addition, by distributing the conductive particles 12 unevenly on the metal layer 20 side in this manner, the capture rate of the conductive particles 12 in the wiring (electrodes) or the like can be improved. In other words, the conduction can be made more stable.

[0106] Moreover, the wiring forming member 1, 1c, 1e may further include a release film. The release film may be attached to the adhesive layer 10, 10c, 10d on the side opposite to the side to which the metal layer 20 is attached, or may be attached to the side of the metal layer 20 opposite to the side to which the adhesive layer 10, 10c, 10d is attached, or may be attached to both of these. Also, the first surface 20a of the metal layer 20 may be attached to the adhesive layer 10, 10c, 10d. In this case, the wiring forming member becomes easier to handle, and the work efficiency when forming a wiring layer using the wiring forming member can be improved.

[0107] In addition, although the above description has been given by taking as an example a case where the wiring-forming member is a member formed by bonding the adhesive layer 10 and the metal layer 20, the wiring-forming member in this embodiment may be configured as a set product in which the adhesive layer 10 and the metal layer 20 are provided as separate bodies, and the adhesive layer 10 can be bonded to the first surface 20a of the metal layer 20 during use. In this case, since the adhesive layer 10 and the metal layer 20 can be prepared separately (as a set of wiring-forming members), it becomes possible to improve the degree of freedom of work when fabricating a wiring layer using the wiring-forming member, such as by selecting a wiring-forming member with a more optimal material composition.

[0108] The adhesive film with metal layer of this embodiment may have an adhesive layer including a first adhesive layer containing copper particles and an adhesive component, and a second adhesive layer containing an adhesive component. Such an adhesive film with metal layer can also be used to form wiring. Hereinafter, the details of the adhesive film with metal layer having the above configuration will be described with reference to the case where it is used as a wiring forming member.

[0109] Fig. 4 is a cross-sectional view showing a wiring-forming member according to another embodiment of the present disclosure. The wiring-forming member 2 shown in Fig. 4 is configured to include an adhesive layer 10 containing conductive particles 12, and a metal layer 20. The adhesive layer 10 includes a first adhesive layer 15 containing conductive particles 12 and an adhesive component 14, and a second adhesive layer 16 containing an adhesive component 17.

[0110] The first adhesive layer 15 contains conductive particles 12 and an insulating adhesive component 14 in which the conductive particles 12 are dispersed. The adhesive component 14 is the same as that described above.

[0111] The second adhesive layer 16 includes an insulating adhesive component 17. The insulating adhesive component 17 in the second adhesive layer 16 may be the same as or different from the adhesive component 14. The adhesive component 17 in the second adhesive layer 16 is defined as a solid content other than conductive particles. The second adhesive layer 16 may be in a B-stage state, i.e., a semi-cured state, before the wiring layer is formed by the wiring-forming member 2.

[0112] In this embodiment, the reactivity of the first adhesive layer 15 and the second adhesive layer 16 is adjusted so that the adhesive layer 10 has the above-mentioned reaction rate, and the average particle size of the conductive particles 12 and the thicknesses of the first adhesive layer 15 and the second adhesive layer 16 may be adjusted so that the ratio [Dp / T] of the average particle size Dp of the conductive particles 12 to the thickness T of the adhesive layer 10 is within the above-mentioned range.

[0113] The thickness d1 of the first adhesive layer 15 may be 0.56 to 1.2 times the average particle diameter Dp of the conductive particles 12, or 0.56 to 1.0 times, or 0.56 to 0.80 times.

[0114] The thickness of the first adhesive layer 15 may be 1 to 70 μm, may be 1 to 60 μm, or may be 1 to 50 μm.

[0115] The thickness of the second adhesive layer 16 may be 0 to 50 μm, may be 0 to 40 μm, or may be 0 to 30 μm.

[0116] Next, a method for forming a wiring layer using the above-mentioned wiring formation member 2 will be described with reference to Fig. 5. Fig. 5(a) to (d) are diagrams showing a method for forming a wiring layer using the wiring formation member shown in Fig. 4.

[0117] First, as shown in Fig. 5(a), a wiring-forming member 2 is prepared. Furthermore, a base material 30 on which wiring 32 is formed is prepared. Then, the wiring-forming member 2 is arranged so that the adhesive layer 10 side of the wiring-forming member 2 faces the base material 30. Thereafter, as shown in Fig. 5(b), lamination is performed so as to cover the wiring 32, and the wiring-forming member 2 is attached onto the base material 30.

[0118] Next, as shown in FIG. 5(c), the wiring forming member 2 is heated and pressed to a predetermined extent, and is bonded to the base material 30. At this time, if the first surface 20a of the metal layer 20 of the wiring forming member 2 is flat, the conductive particles 12 that need to ensure electrical conductivity can be more reliably deformed into flat conductive particles 12a. In the wire forming member 2a bonded to the wire 32, the flattened conductive particles 12a (whereby the insulating layer is broken and the conductive portion is exposed) are arranged, and good electrical conduction between the metal layer 20 and the wiring 32 is achieved. At this time, the adhesive layer 10 is also crushed to become a thinner adhesive layer 10B. In addition, since the adhesive layer 10 includes the first adhesive layer 15 in which the conductive particles are contained in the adhesive component, and the second adhesive layer 16, good insulation reliability is achieved in the thickness direction of the portion where electrical connection is not desired.

[0119] Next, as shown in Fig. 5(d), the metal layer 20 is subjected to a predetermined patterning process (e.g., etching process) to process it into a predetermined wiring pattern 20c (another wiring). At this time, the second surface 20b of the metal layer 20 may be processed to have a smooth surface. The above-mentioned processes in Fig. 5(a) to (d) may be repeated a predetermined number of times to form a wiring layer.

[0120] That is, a method for forming a wiring layer using a wiring forming member includes the steps of preparing a wiring forming member, preparing a base material on which wiring is formed, placing the wiring forming member on the surface of the base material on which wiring is formed so that the adhesive layer side faces the substrate and covers the wiring, heating and pressing the wiring forming member to the base material, and performing a patterning process on the metal layer.

[0121] In this manner, the wiring-forming member 2b is formed. The wiring-forming member 2b includes a base material 30 having wiring 32, and a cured product (adhesive layer of the wiring-forming member bonded by heating and pressure) of the first adhesive layer 15 and the second adhesive layer 16 of the wiring-forming member 2 arranged on the base material 30 so as to cover the wiring 32. In the wiring-forming member 2b, the wiring 32 and the metal layer 20 of the wiring-forming member 2 or the wiring pattern 20c formed (for example, by etching) from the metal layer 20 are electrically connected by the conductive particles 12a. When the processes (a) to (d) of FIG. 5 are repeated a predetermined number of times, the wiring-forming member 2b may have a configuration having a plurality of wiring layers (layers in which the above-mentioned wirings are connected to each other).

[0122] Thus, according to the method for forming a wiring layer using the wiring formation member 2 according to this embodiment, the process for forming a wiring layer connecting between wirings can be simplified compared to the conventional process of performing laser processing and filling plating, etc. Also, it becomes possible to easily thin the formed wiring layer.

[0123] Furthermore, according to the method for forming a wiring layer using the wiring formation member 2 of this embodiment, when the adhesive layer 10 has the above-mentioned reaction rate and the ratio [Dp / T] of the average particle size Dp of the conductive particles 12 to the thickness T of the adhesive layer 10 is 0.56 to 1.2, a wiring layer in which resistance unevenness is suppressed can be formed.

[0124] Furthermore, according to the method for forming a wiring layer using the wiring formation member 2 of this embodiment, the following effects can ensure sufficient freedom in designing the wiring pattern when forming the wiring layer. (i) By including the second adhesive layer 16 in the adhesive layer 10, even if the wiring layer formed by patterning the metal layer 20 has a portion in the stacking direction (or the thickness direction of the adhesive layer) where no conductive connection is desired, it becomes easy to ensure insulation reliability in that portion. (ii) In the wiring layer formed by patterning the metal layer 20 or in the rewiring formed separately, the conductive particles 12 are less likely to come into contact with parts other than the parts that are electrically connected, making it easier to suppress electrical transmission loss in the wiring due to contact of the conductive particles.

[0125] The above effects will be described with reference to the drawings.

[0126] 6(a) and 6(b) are cross-sectional views for explaining an example of a case where a wiring layer is formed using the wiring formation member 2 according to this embodiment.

[0127] 6(a) shows a state in which a substrate 30 having a wiring pattern 32a and a wiring pattern 32b is prepared, and a wiring-forming member 2 is placed on the surface of the substrate 30 on which the wiring patterns are formed so as to cover the wiring patterns 32a and 32b, with the adhesive layer 10 side facing the substrate 30. Thereafter, a process of heat-pressing the wiring-forming member 2 to the substrate 30 and a process of patterning the metal layer 20 are performed, thereby obtaining a wiring-forming member having a wiring pattern 20d that is conductively connected to the wiring pattern 32a and a wiring pattern 20e that is not intended to be conductively connected to the wiring pattern 32b, as shown in FIG. 6(b).

[0128] Here, the adhesive layer 10 of the wiring forming member 2 includes a first adhesive layer 15 containing conductive particles 12 and an adhesive component 14, and a second adhesive layer 16 containing no conductive particles and containing an adhesive component 17. This ensures good electrical continuity between the wiring pattern 20d and the wiring pattern 32a via the conductive particles 12 when pressed together, while providing an adhesive layer 18a with a thickness that ensures a distance between the wiring pattern 20e and the wiring pattern 32b that are not desired to be electrically connected, such that no electrical continuity occurs due to the conductive particles 12. This prevents the wiring pattern 20e and the wiring pattern 32b from being electrically connected, ensuring insulation reliability in the thickness direction of the adhesive layer.

[0129] 7(a) and 7(b) are cross-sectional views for explaining another example in which a wiring layer is formed using the wiring formation member 2 according to this embodiment.

[0130] 7(a) shows a state in which a substrate 30 having a wiring pattern 32a is prepared, and a wiring-forming member 2 is placed on the surface of the substrate 30 on which the wiring pattern is formed so that the adhesive layer 10 side faces the substrate 30 to cover the wiring pattern 32a. After this, a process of thermocompression bonding the wiring-forming member 2 to the substrate 30 and a process of patterning the metal layer 20 are performed, thereby obtaining a wiring-forming member having a wiring pattern 20d conductively connected to the wiring pattern 32a and a wiring pattern 20f that is not conductively connected (or a portion of the wiring pattern that is not conductively connected) as shown in FIG. 7(b).

[0131] Here, the adhesive layer 10 of the wiring forming member 2 includes the first adhesive layer 15 containing the conductive particles 12 and the adhesive component 14, and the second adhesive layer 16 containing no conductive particles and containing the adhesive component 17. This allows the adhesive layer 18a to be provided so that the wiring pattern 20f and the conductive particles 12 do not come into contact with each other while ensuring good conduction between the wiring pattern 20d and the wiring pattern 32a through the conductive particles 12 when pressed together. This makes it possible to suppress the transmission loss of the wiring caused by the contact of the conductive particles in the wiring pattern 20f. In particular, in the wiring forming member 2, the metal layer 20, the second adhesive layer 16, and the first adhesive layer 15 are laminated in this order, making it easy to prevent the wiring pattern 20f from coming into contact with the conductive particles 12.

[0132] In the method shown in FIG. 7, the wiring pattern 20f may be formed by a step of performing a patterning process on the metal layer 20 and a step of forming rewiring.

[0133] In the first adhesive layer 15 of the wiring formation member 2 shown in FIG. 4, the conductive particles 12 are arranged locally, but the conductive particles 12 may also be dispersed randomly or evenly within the adhesive component 14.

[0134] In addition, in the first adhesive layer 15 of the wiring formation member 2, the conductive particles 12 may be locally arranged on the second adhesive layer 16 side, or the conductive particles 12 may be locally arranged on the opposite side to the second adhesive layer 16 side (the second surface 10b side of the adhesive layer 10).

[0135] In addition, the second adhesive layer 16 of the wiring formation member 2 does not contain conductive particles, but the second adhesive layer 16 may contain a portion of the particle body of the conductive particle 12 (in other words, it does not have to contain the entire particle body of the conductive particle 12).

[0136] The adhesive layer 10 of the wiring-forming member 2 may be composed of two layers, the first adhesive layer 15 and the second adhesive layer 16, or may be composed of three or more layers including a layer other than the first adhesive layer 15 and the second adhesive layer 16 (for example, a third adhesive layer). The third adhesive layer may be a layer having a composition similar to the composition described above for the first adhesive layer 15 or the second adhesive layer 16, and may be a layer having a thickness similar to the thickness described above for the first adhesive layer 15 or the second adhesive layer 16. For example, the wiring-forming member 2 may be configured by laminating a metal layer, a third adhesive layer, a second adhesive layer, and a first adhesive layer in this order, or may be configured by laminating a metal layer, a second adhesive layer, a first adhesive layer, and a third adhesive layer in this order, but is not limited thereto.

[0137] The wiring-forming member 2 may further include a release film. The release film may be attached to the side of the adhesive layer 10 opposite to the side to which the metal layer 20 is attached (the second surface 10b side of the adhesive layer 10), or may be attached to the side of the metal layer 20 opposite to the side to which the adhesive layer 10 is attached (the first surface 20a of the metal layer) (the second surface 20b side of the metal layer 20), or may be attached to both of these. In this case, the wiring-forming member becomes easier to handle, and the work efficiency when forming a wiring layer using the wiring-forming member can be improved.

[0138] In addition, although the above description has been given by taking as an example a case where the wiring-forming member is a member formed by bonding the adhesive layer 10 and the metal layer 20, the wiring-forming member 2 in this embodiment may be configured as a set product in which the adhesive layer 10 and the metal layer 20 are provided as separate bodies, and the adhesive layer 10 can be bonded to the first surface 20a of the metal layer 20 during use. In this case, since the adhesive layer 10 and the metal layer 20 can be prepared separately (as a set of wiring-forming members), it becomes possible to improve the degree of freedom in the work when fabricating a wiring layer using the wiring-forming member, such as by selecting a wiring-forming member having a more optimal material composition.

[0139] An adhesive film according to an embodiment of the present disclosure contains conductive particles and a thermosetting resin composition, and has a thermal expansion coefficient of 1.5 to 3% when the cured product of the adhesive film is heated from 40° C. to 260° C. The cured product of the adhesive film can be prepared in the same manner as the cured product of the adhesive layer described above, and the thermal expansion coefficient can be measured in the same manner.

[0140] The adhesive film according to this embodiment may have a configuration similar to that of the adhesive layer in the wiring formation member described above.

[0141] The adhesive film according to the present embodiment can be produced by the following method. Specifically, first, a thermosetting resin composition and conductive particles are added to a solvent (organic solvent), and dissolved or dispersed by stirring, mixing, kneading, etc. to prepare a varnish composition (varnish-like adhesive composition). Thereafter, the varnish composition is applied to a substrate that has been subjected to a release treatment using a knife coater, roll coater, applicator, comma coater, die coater, etc., and the solvent is volatilized by heating to form an adhesive film on the substrate.

[0142] The solvent used in preparing the varnish composition may be a solvent that has the property of dissolving or dispersing each component uniformly. Examples of such solvents include toluene, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, propyl acetate, and butyl acetate. These solvents can be used alone or in combination of two or more. The stirring and mixing and kneading in preparing the varnish composition can be performed using, for example, a stirrer, a grinding machine, a three-roll mill, a ball mill, a bead mill, or a homodisper.

[0143] The substrate is not particularly limited as long as it has heat resistance sufficient to withstand the heating conditions for volatilizing the solvent. For example, substrates (e.g., films) made of oriented polypropylene (OPP), polyethylene terephthalate (PET), polyethylene naphthalate, polyethylene isophthalate, polybutylene terephthalate, polyolefin, polyacetate, polycarbonate, polyphenylene sulfide, polyamide, polyimide, cellulose, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinylidene chloride, synthetic rubber, liquid crystal polymer, etc. can be used.

[0144] The adhesive film according to the present embodiment can be used to connect circuit members, and can be suitably used as an adhesive film for circuit connection for connecting a first circuit member having a first electrode (e.g., a first circuit member having a first circuit electrode formed on the main surface of a first substrate) and a second circuit member having a second electrode (e.g., a second circuit member having a second circuit electrode formed on the main surface of a second substrate) in a state in which the first electrode and the second electrode (the first circuit electrode and the second circuit electrode) are arranged opposite each other. The adhesive film according to the present embodiment can improve the conductivity between the electrodes in the circuit connection structure.

[0145] Examples of the first circuit member and the second circuit member include chip components such as semiconductor chips, resistor chips, and capacitor chips, and substrates such as printed circuit boards. EXAMPLES

[0146] The present disclosure will be described in more detail below with reference to examples, although the present disclosure is not limited to these examples.

[0147] <Preparation of adhesive component (thermosetting resin composition)> As adhesive components, the following thermosetting components and fillers were prepared. (thermosetting component) Epoxy resin A: NC-3000H (biphenylaralkyl type epoxy resin, product name, manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent: 289g / eq) Epoxy resin B: YL983U (bisphenol F type epoxy resin, Mitsubishi Chemical Corporation, product name, epoxy equivalent: 170g / eq) Epoxy resin C: HP-4700 (naphthalene-type multifunctional epoxy resin, product name, manufactured by DIC Corporation, epoxy equivalent: 165 g / eq) Epoxy resin D: jER-630 (multifunctional epoxy resin, Mitsubishi Chemical Corporation, product name, epoxy equivalent: 98g / eq) Phenolic resin A: KA-1160 (cresol novolac type phenolic resin, product name, manufactured by DIC Corporation, hydroxyl equivalent: 117 g / eq) The hydroxyl equivalent of the phenolic resin was determined by the following measurement method. Phenolic resin B: KA-1163 (cresol novolac type phenolic resin, product name, manufactured by DIC Corporation, hydroxyl equivalent: 118 g / eq) The hydroxyl equivalent of the phenolic resin was determined by the following measurement method. Phenolic resin C: KA-1165 (cresol novolac type phenolic resin, product name, manufactured by DIC Corporation, hydroxyl equivalent: 119 g / eq) The hydroxyl equivalent of the phenolic resin was determined by the following measurement method. Phenoxy resin A: YP-70 (BPA / BPF copolymer type, product name, manufactured by Nippon Steel Chemical & Material Co., Ltd.) Curing accelerator A: G-8009L (isocyanate masked imidazole, product name, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) (Filler) Silica particles A: SC-2050KC (phenylaminosilane-treated silica filler, average particle size 0.5 μm, manufactured by Admatechs Co., Ltd., product name)

[0148] <Method for measuring hydroxyl equivalent> 1 g of sample was precisely weighed into a round-bottom flask, and 5 mL of acetic anhydride and pyridine test solution were precisely weighed. Next, an air condenser was attached to the flask and it was heated at 100°C for 1 hour. After cooling the flask, 1 mL of water was added, and the flask was heated again at 100°C for 10 minutes. After cooling the flask again, the air condenser and the neck of the flask were washed with 5 mL of neutralized methanol, and 1 mL of phenolphthalein reagent was added. The solution thus obtained was titrated with 0.1 mol / L potassium hydroxide-ethanol solution to determine the hydroxyl value. From the obtained hydroxyl value, the hydroxyl equivalent (g / eq) converted to the mass per 1 mole (1 eq) of hydroxyl groups was calculated.

[0149] <Preparation of conductive particles> The following conductive particles were prepared. (Conductive Particles 1) As the conductive particles 1, Cu particles (manufactured by Mitsui Mining & Smelting Co., Ltd., product name "MA-CJU", average particle size 20 μm, specific gravity 8.9) were prepared. (Conductive particles 2) As the conductive particles 2, Cu particles (manufactured by Mitsui Mining & Smelting Co., Ltd., product name "MA-CKU", average particle size 10 μm, specific gravity 8.9) were prepared.

[0150] <Conductive particle properties> The amount of change and the amount of recovery when a pressure of 50 mN was applied per particle were measured by a microcompression test using a probe under the following conditions. Measurement device: "FISCHERSCOPE HM2000" (manufactured by Fisher Instruments) Probe size (area): 100 μm x 100 μm Pressing time: Press for 50 seconds / Return for 50 seconds Measurement temperature: 25℃ Thrust: 50mN The change and recovery of the conductive particles 1 were 3.39 μm and 0.15 μm, respectively. The change and recovery of the conductive particles 2 were 4.86 μm and 0.13 μm, respectively.

[0151] <Preparation of wiring forming member> Example 1 5.00 g of epoxy resin A, 4.69 g of epoxy resin B, 4.08 g of phenolic resin B, 2.68 g of phenoxy resin A, and 0.025 g of curing accelerator A were dissolved in 19.1 g of methyl ethyl ketone (MEK), and then 5.36 g of silica particles A and 4.21 g of conductive particles 1 were added to prepare a coating liquid for forming an adhesive layer.

[0152] This coating solution was applied to one side (surface roughness Rz: 3.0 μm) of a copper foil (manufactured by Mitsui Mining & Smelting, product name "3EC-M3-VLP", thickness: 12 μm) using a coating device (manufactured by Yasui Seiki Co., Ltd., product name: Precision Coater), and dried with hot air at 70° C. for 5 minutes to provide an adhesive layer with a thickness of 25 μm on the copper foil. In this way, the wiring-forming member of Example 1 was produced.

[0153] (Examples 2 to 11, Comparative Examples 1 to 3) Each wiring-forming member was produced in the same manner as in Example 1, except that a coating solution for forming an adhesive layer was prepared with the composition and blending amount shown in Table 1 or Table 2, and an adhesive layer was formed with the thickness shown in Table 1 or Table 2.

[0154] [Thermal expansion coefficient when the cured adhesive layer is heated from 40℃ to 260℃] The thermal expansion coefficient of the cured adhesive layer was measured by the following procedure. [Preparation of cured product] (1) Before heating, a portion of the adhesive layer was scraped off and 0.60 g was weighed out as an evaluation sample. (2) Prepare a silicone sheet that is 100 mm long, 100 mm wide, and 1 mm thick, and cut out a portion of this sheet to measure 5 mm x 40 mm x 1 mm. (3) Place the pre-heating evaluation sample measured in (1) into the cut-out portion of the silicone sheet. (4) The silicone sheet containing the pre-heating evaluation sample is heated and pressurized for 60 minutes at 180° C. and 2 MPa using a thermocompression bonding device to produce a cured product of the pre-heating evaluation sample. [Measurement of thermal expansion coefficient of cured product] (1) The cured product of the pre-heated evaluation sample prepared above is cut into a piece measuring 5 mm x 5 mm x 1 mm to prepare an evaluation sample. (2) Using a thermomechanical analysis (TMA) device (measurement mode: compression), measure the change in thickness when the evaluation sample is heated from 40°C to 260°C at a heating rate of 5°C / min, and calculate the thermal expansion coefficient using the following formula. Thermal expansion coefficient (%) = (thickness at 260°C - thickness at 40°C) x 100 / (thickness at 40°C)

[0155] [Measurement of reaction rate when heated at 180℃ for 5 minutes] The reaction rate of the adhesive layer prepared above was determined when it was heated at 180°C for 5 minutes according to the following method. A part of the adhesive layer was scraped off to obtain two 5 mg samples for evaluation before heating. Next, one of the samples for evaluation before heating was heated at 180°C for 5 minutes to obtain a sample for evaluation after heating. The DSC calorific value of each of the samples for evaluation before heating and the samples for evaluation after heating was measured under a nitrogen gas flow at a measurement temperature range of 30°C to 250°C and a heating rate of 10°C / min using a differential scanning calorimeter (DSC7, manufactured by PERKIN ELMER). Based on the measured DSC calorific value, the reaction rate when heated at 180°C for 5 minutes was calculated from the following formula. Reaction rate = (Cx-Cy) x 100 / Cx [In the formula, Cx represents the DSC calorific value (J / g) of the evaluation sample before heating, and Cy represents the DSC calorific value (J / g) of the evaluation sample after heating.]

[0156] [Evaluation of wiring forming materials] For the wiring forming members prepared above, evaluation samples were prepared according to the following method, and their connection resistance values ​​were measured. The connection resistance values ​​were evaluated according to the following criteria.

[0157] [Connection resistance measurement] <Preparation of evaluation samples> The wiring member was attached to a printed wiring board (PWB) with three copper circuits, each 1000μm wide, 10000μm pitch, and 15μm thick, on a glass cloth epoxy board. This was connected over a width of 2mm by heating and pressurizing at 180℃ and 2MPa for 60 minutes using a thermocompression bonding device (heating method: constant heat type, manufactured by Toray Engineering Co., Ltd.), to produce a connection over a width of 2mm.

[0158] The prepared connector with the resist formed on it was immersed in an etching solution and swung. The etching solution was adjusted to copper chloride: 100g / L and hydrochloric acid: 100ml / L. When the desired copper foil area was gone, the connector was washed with pure water. The resist was then peeled off to obtain the desired evaluation sample.

[0159] <Evaluation of evaluation sample (initial)> The resistance between the remaining copper foil on the circuit and the copper circuit on the board was measured with a multimeter immediately after bonding. The connection resistance was calculated as the average of 37 resistance points between the remaining copper foil on the circuit and the copper circuit on the board, and was evaluated according to the following criteria.

[0160] [Connection resistance value judgment criteria] A: The average resistance value is 5mΩ or less B: Average resistance value is over 5mΩ and 10mΩ or less C: The average resistance value is more than 10mΩ

[0161] <Evaluation of evaluation sample (after reflow test)> The evaluation sample was subjected to a reflow process having the following temperature profile three times, and then the connection resistance was measured in the same manner as above and evaluated according to the above criteria. Temperature profile: Heat from 50°C to 150°C at a rate of 2°C / sec, hold at 150°C for 100 seconds, then heat from 150°C to 245°C at a rate of 1°C / sec, hold at 245°C for 50 seconds, then cool from 245°C to 40°C.

[0162] [Mandrel test] The members for forming wiring produced in the examples and comparative examples were subjected to a mandrel test in accordance with JIS K5600-5-1.

[0163] [Table 1]

[0164] [Table 2] [Explanation of symbols]

[0165] 1, 1a, 1c, 1e...wiring forming member, 1d, 1f...wiring layer, 1b...wiring forming member, 2...wiring forming member, 10, 10c, 10d, 10A, 10B...adhesive layer, 10a...first surface, 10b...second surface, 10e...first adhesive layer, 10f...second adhesive layer, 12, 12a...conductive particles, 14...adhesive component, 15...first adhesive layer, 16...second adhesive layer, 17...adhesive component, 20...metal layer, 20a...first surface, 20b...second surface, 30...substrate, 32...wiring.

Claims

1. An adhesive film containing conductive particles and a thermosetting resin composition, The adhesive film has a thermal expansion coefficient of 1.5 to 3% when the cured product of the adhesive film is heated from 40°C to 260°C.

2. 2. The adhesive film according to claim 1, which has a reaction rate of 90% or less when heated at 180°C for 5 minutes.

3. The adhesive film of claim 1 , wherein the conductive particles comprise copper particles.

4. A metal layer and an adhesive layer disposed on the metal layer, The adhesive layer contains conductive particles and a thermosetting resin composition, The adhesive film with a metal layer has a thermal expansion coefficient of 1.5 to 3% when the cured product of the adhesive layer is heated from 40°C to 260°C.

5. 5. The adhesive film with a metal layer according to claim 4, wherein the adhesive layer has a reaction rate of 90% or less when heated at 180°C for 5 minutes.

6. The adhesive film with a metal layer according to claim 4 , wherein the conductive particles include copper particles.

7. The adhesive film with a metal layer according to claim 4 or 5, which is used for forming wiring.

8. A wiring-forming member, comprising an adhesive layer and a metal layer provided as separate bodies, the adhesive layer being capable of adhering to the metal layer during use, The adhesive layer includes conductive particles and a thermosetting resin composition, The wiring-forming member has a thermal expansion coefficient of 1.5 to 3% when the cured product of the adhesive layer is heated from 40°C to 260°C.

9. 9. The member for forming wiring according to claim 8, wherein the adhesive layer has a reaction rate of 90% or less when heated at 180°C for 5 minutes.

10. The member for forming wiring according to claim 8 , wherein the conductive particles include copper particles.

11. A step of preparing an adhesive film with a metal layer according to any one of claims 4 to 6; A step of preparing a substrate on which wiring is formed; a step of placing the metal layer-attached adhesive film on the surface of the base material on which the wiring is formed so as to cover the wiring, with the adhesive layer facing the base material; a step of heat-pressing the metal layer-attached adhesive film to the substrate; performing a patterning process on the metal layer; A method for forming a wiring layer comprising:

12. A step of preparing a wiring forming member according to any one of claims 8 to 10; A step of preparing a substrate on which wiring is formed; a step of placing the wiring forming member on a surface of the base material on which the wiring is formed so as to cover the wiring, with the adhesive layer facing the base material; a step of heat-pressing the wiring forming member onto the base material; performing a patterning process on the metal layer; A method for forming a wiring layer comprising:

13. A substrate having wiring; A cured product of the adhesive layer of the metal layer-attached adhesive film according to any one of claims 4 to 6, which is disposed on the substrate so as to cover the wiring; and Equipped with A wiring-forming member, in which the wiring is electrically connected to the metal layer of the metal layer-attached adhesive film or to another wiring formed from the metal layer.

14. A substrate having wiring; A cured product of the adhesive layer of the wiring formation member according to any one of claims 8 to 10, which is disposed on the base material so as to cover the wiring; Equipped with A wiring-forming member, in which the wiring is electrically connected to the metal layer of the wiring-forming member or to another wiring formed from the metal layer.

Citation Information

Patent Citations

  • Manufacturing method of printed wiring board

    JP2012191204A